A case study of convective organization into precipitating lines in the Southwest Amazon during the WETAMC and TRMM-LBA - Dias, M. A. F. S.; Petersen, W.; Dias, P. L. S.; Cifelli, R.; Betts, A. K.; Longo, M.; Gomes, A. M. [UNESP]; Fisch, G. F.; Lima, M. A. [UNESP]; Antonio, M. A. [UNESP]; Albrecht, R. I. (Amer Geophysical Union, 2002)
A case study of convective development in the Southwest Amazon region during the Wet Season Atmospheric Mesoscale Campaign (WETAMC) and Tropical Rainfall Measuring Mission (TRMM)/Large-Scale Biosphere-Atmosphere (LBA) Experiment in Amazonia is presented. The convective development during 7 February 1999 is shown to occur during a period of very weak large-scale forcing in the presence of topography and deforestation. The available data include dual Doppler radar analysis, radiosonde launches, and surface and boundary layer observations. The observational analysis is complemented with a series of model simulations using the RAMS with 2-km resolution over a 300 km 300 km area forced by a morning radiosonde profile. A comparison of the observed and simulated thermodynamic transformation of the boundary layer and of the formation of convective lines, and of their kinematic and microphysical properties is presented. It is shown that only a few very deep and intense convective cells are necessary to explain the overall precipitating line formation and that discrete propagation and coupling with upper atmosphere circulations may explain the appearance of several lines. The numerical simulation indicates that topography may be the cause of initial convective development, although later on the convective line is parallel to the midlevel shear. There are indications that small-scale deforestation may have an effect on increasing rainfall in the wet season when the large-scale forcing is very weak.